The Influence of Fraud Triangle Elements on Indications of Financial Statement Fraud in Non-Financial State-Owned Enterprises in Indonesia During the 2021–2024 Period - Rizaya, Agung; Nurhazana (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
This study examines the influence of Fraud Triangle elements pressure, opportunity, and rationalization on indications of financial statement fraud in non-financial State-Owned Enterprises (SOEs) in Indonesia during the 2021–2024 period. Financial statement fraud is proxied by discretionary accruals (DACC), while pressure, opportunity, and rationalization are measured using return on assets (ROA), total asset change (ACHANGE), leverage (LEV), proportion of independent commissioners (BDOUT), receivables to sales ratio (REC), and audit opinion (AO). Using secondary data from 80 firm-year observations of audited financial statements, this study applies multiple linear regression analysis. The results indicate that pressure variables (ROA, ACHANGE, and LEV) and rationalization (AO) have a significant effect on DACC, whereas opportunity variables (BDOUT and REC) show no significant effect. Simultaneously, all variables significantly influence indications of financial statement fraud. This study contributes theoretically by reinforcing the relevance of the Fraud Triangle framework in explaining fraud risk within non-financial SOEs, and practically by providing insights for auditors, regulators, and SOE management to strengthen fraud risk assessment and internal control mechanisms.